EFEKTIVITAS MODEL PEMBELAJARAN PASPOR (PAIRING, SQUARE, PRESENTATION, REPITATION) TERHADAP HASIL BELAJAR SISWA KELAS X IPA SMA NEGERI 2 RAMBAH - Sultan Hasibuan; Jufri, Jufri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of 21st-century education requires learning models that can enhance students’ critical thinking, problem-solving skills, and active engagement. However, based on observations at SMA Negeri 2 Rambah, approximately 62.5% of students had not achieved the Minimum Mastery Criteria (KKM), and student participation in learning activities was relatively low. This study aims to determine the effect of the PASPOR learning model (Pairing, Square, Presentation, Repetition) on students’ learning outcomes in Informatics. This research employed a quantitative approach with a pre-experimental design using a one-group pretest-posttest design. The sample consisted of 21 students of class X IPA selected through purposive sampling. Data collection instruments included essay tests, observation sheets, and student response questionnaires. Data were analyzed using the Wilcoxon Signed-Rank Test, N-Gain, and Cohen’s d. The results showed a significant difference between pretest and posttest scores with a significance value of 0.000 < 0.05. The N-Gain value was 0.6327 (moderate category), while Cohen’s d was 2.431 (very large effect size). In addition, the implementation of the model reached 90.28%, student activity was 88.69%, and student responses were 88.69%, all categorized as very good. These findings indicate that the PASPOR learning model is effective in improving student learning outcomes and engagement. Therefore, this model can be used as an alternative instructional strategy to support active learning and achieve curriculum objectives.